A comparative study of physical image quality in digital and synthetic mammography from commercially available mammography systems. (22nd August 2018) - Baldelli, Paola; Bertolini, Marco; Contillo, Adriano; Della Gala, Giuseppe; Golinelli, Paola; Pagan, Laura; Rivetti, Stefano; Taibi, Angelo
Abstract: We present a comparison between full field digital mammography and synthetic mammography, performed on several mammography systems from four different manufacturers. The analysis is carried out on both the digital and synthetic images of two commercially available mammography phantoms, and focuses on a set of objective metrics that encode the geometrical appearance of imaging features of diagnostic interest. In particular, we measured sizes and contrasts of several clusters of microcalcification specks, shapes and contrasts of circular masses, and the power spectrum of background regions mimicking the heterogeneous texture of the breast parenchyma. Despite the potential issues of tomosynthesis in terms of image blurring, the synthetic images do not highlight any globally significant differences in the rendering of the details of interest, when compared to the original digital mammograms: relative contrasts are generally preserved, as well as the geometry of broad structures. We conclude that, as far as the considered objective metrics are concerned, the image quality of synthetic mammography does not exhibit significant differences with respect to the one of full field digital mammography, for all the considered systems.